Study on Cutting of Sawlogs by Power Chain Saws in West Beiligal - Mitra, S. K. (Indian Forester, 1979)
In India Power Chain Saws have been introduced in recent years for felling and conversion of trees. These saws are presently imported from developed countries like Sweden, U.S.A, and W. Germany and consequently a number of models of these saws are available. It was felt necessary to investigate the relative suitability and economics of these commonly available power chain saws for a specific stump area operation. Accordingly a detailed time and cost was undertaken in the foothill forests of Kalimpong Division in West Bengal where power chain saws are being used in fairly extensive scale by professional operators sponsored by the forest development corporation of West Bengal. Three models viz Partner R-12 Poulan 245A and Mc Culloch ProMac 60 were compared for felling and conversion of miscellaneous softwood species for the preparation of plywood logs. The study concludes that Partner R-12 power chain saw is the most suitable equipment compared to the other two. The details of production economics, cutting speed and cost of operation have been derived and discussed in support of the inference drawn.